GPI7‐mediated glycosylphosphatidylinositol anchoring regulates appressorial penetration and immune evasion during infection of Magnaporthe oryzae. (21st February 2020) - Liu, Caiyun; Xing, Junjie; Cai, Xuan; Hendy, Ahmed; He, Wenhui; Yang, Jun; Huang, Junbing; Peng, You‐Liang; Ryder, Lauren; Chen, Xiao‐Lin
Summary: Glycosylphosphatidylinositol (GPI) anchoring plays key roles in many biological processes by targeting proteins to the cell wall; however, its roles are largely unknown in plant pathogenic fungi. Here, we reveal the roles of the GPI anchoring in Magnaporthe oryzae during plant infection. The GPI‐anchored proteins were found to highly accumulate in appressoria and invasive hyphae. Disruption of GPI7, a GPI anchor‐pathway gene, led to a significant reduction in virulence. The Δ gpi7 mutant showed significant defects in penetration and invasive growth. This mutant also displayed defects of the cell wall architecture, suggesting GPI7 is required for cell wall biogenesis. Removal of GPI‐anchored proteins in the wild‐type strain by hydrofluoric acid (HF) pyridine treatment exposed both the chitin and β‐1, 3‐glucans to the host immune system. Exposure of the chitin and β‐1, 3‐glucans was also observed in the Δ gpi7 mutant, indicating GPI‐anchored proteins are required for immune evasion. The GPI anchoring can regulate subcellular localization of the Gel proteins in the cell wall for appressorial penetration and abundance of which for invasive growth. Our results indicate the GPI anchoring facilitates the penetration of M. oryzae into host cells by affecting the cell wall integrity and the evasion of host immune recognition.